Factors contributing to job satisfaction amongst secondary school ESL teachers in the district of Marang, Terengganu / Erny Suriaty Ezudin - Ezudin, Erny Suriaty (2014)
Job satisfaction is very important to bring a better working performance for ESL teachers in ensuring the future generation will succeed in their undertakings. The purpose of this study is to define the best factor that contributes to ESL teachers’ job satisfaction. Forty-four ESL teachers from 13 secondary schools in Marang, Terengganu were selected as the respondents. In this study, 4 variable factors namely: co-workers factor, management policy factor, promotion factor and working environment factor were chosen to correlate with job satisfaction. The finding showed that all of the factors revealed a moderate correlation with job satisfaction. In a nutshell, the finding of this study showed that working environment factor is defined as the best factor among the other three factors that correlated to a better job satisfaction for the teachers. The results showed that 47% of its variability with the overall job satisfaction of the ESL teachers in the District of Marang, Terengganu.